An experimental study of a Mediterranean diet intervention for patients with rheumatoid arthritis - Skoldstam, L (2003)
Objective: To investigate the efficacy of a Mediterranean diet (MD) versus an ordinary Western diet for suppression of disease activity in patients with rheumatoid arthritis (RA). Methods: Patients with well controlled, although active RA of at least two years' duration, who were receiving stable pharmacological treatment, were invited to participate. All patients were randomly allocated to the MD or the control diet (CD). To achieve good compliance with prescribed diets all patients were for the first three weeks served the MD or the CD, respectively, for lunch and dinner at the outpatient clinic's canteen. Clinical examinations were performed at baseline, and again in the 3rd, 6th, and 12th week. A composite disease activity index (DAS28), a physical function index (Health Assessment Questionnaire (HAQ)), a health survey of quality of life (Short Form-36 (SF-36)), and the daily consumption of non-steroidal anti-inflammatory drugs were used as primary efficacy variables. Results: From baseline to the end of the study the patients in the MD group (n=26) showed a decrease in DAS28 of 0.56 (p<0.001), in HAQ of 0.15 (p=0.020), and in two dimensions of the SF-36 Health Survey: an increase in "vitality" of 11.3 (p=0.018) and a decrease in "compared with one year earlier" of 0.6 (p=0.016). For the control patients (n=25) no significant change was seen at the end of the study. This difference between the two treatment groups was notable only in the second half of the trial. Conclusion: The results indicate that patients with RA, by adjusting to a Mediterranean diet, did obtain a reduction in inflammatory activity, an increase in physical function, and improved vitality.